Decrease of time of model synthesis in intellectual monitoring systems - Avramenko, A.S.; Golub, S.V. (Математичні машини і системи, 2019)
The article investigates modern intellectual monitoring systems (IMS), which are able to predict the consequences of the adopted control decisions of decision support systems (DSS), thanks to the modeling of the characteristics of monitored objects. The drawbacks of existing implementations of IMS show when working in crisis monitoring. Since crisis monitoring imposes a number of restrictions on the speed of DSS and the high probability of failure of the trained IMS models, the use of existing implementations of IMS is problematic. The reasons of the existence of these shortcomings, and the algorithms with which it is connected lies in existing methodology. The paper investigates advantages and disadvantages of existing methods for the formation of inter-level relations in the IMS. A particular attention is paid to the method of classification of input data arrays (IDA) according to their characteristics, to the corresponding class of model synthesis algorithm (MSA). This paper proposes to improve the well-known method of classifying MIA by using unique adaptive classifiers for each of the MSA class. У статті досліджено сучасні моніторингові інтелектуальні системи (МІС), які здатні прогнозувати наслідки прийнятих керуючих рішень систем підтримки прийняття рішень (СППР) завдяки моделюванню характеристик об’єктів моніторингу. Продемонстровано недоліки існуючих реалізацій МІС при роботі в умовах кризового моніторингу. Так як кризовий моніторинг накладає ряд обмежень на швидкість роботи СППР та велику вірогідність виходу навчених моделей МІС із строю, то використання існуючих реалізацій МІС є проблематичним. Досліджено причини існування даних недоліків та алгоритми, з якими це пов’язано. Досліджено переваги та недоліки існуючих методів формування міжрівневих зв’язків у МІС. Особливу увагу звернено на метод класифікації масивів вхідних даних (МВД) за їх характеристиками до відповідного класу алгоритмів синтезу моделей (АСМ). Запропоновано вдосконалити відомий метод класифікації масивів вхідних даних за допомогою використання унікальних адаптивних класифікаторів для кожного із класів алгоритмів синтезу моделей із списку реалізованих у системі. В статье исследованы современные мониторинговые интеллектуальные системы (МИС), которые способны прогнозировать последствия принимаемых управляющих решений систем поддержки принятия решений (СППР) благодаря моделированию характеристик объектов мониторинга. Продемонстрированы недостатки существующих реализаций МИС при работе в условиях кризисного мониторинга. Так как кризисный мониторинг накладывает ряд ограничений на скорость работы СППР и большую вероятность выхода обученных моделей МИС из строя, то использование существующих реализаций МИС является проблематичным. Исследованы причины существования данных недостатков и алгоритмы, с которыми это связано. Исследованы преимущества и недостатки существующих методов формирования межуровневых связей в МИС. Особое внимание обращено на метод классификации массивов входных данных (МВД) по их характеристикам к соответствующему классу алгоритмов синтеза моделей (АСМ). Предложено усовершенствовать известный метод классификации МВД посредством использования уникальных адаптивных классификаторов для каждого из классов АСМ.